(untitled) (Revista de Investigaciones Universidad del Quindío, 2017)
This study consisted of determining the efficiency of fermentative yeasts Saccharomyces Cerevisiae and Candida Kefyr hydrolyzate leaves of Eucalyptus Camaldulensis Dehnh. (Myrtaceae) for xylitol production. For the physicochemical characterization of hydrolyzed plant, material humidity, acidity, degrees brix, pH, density, reducing sugars, thermogravimetric analysis (TGA), and infrared were measured.. Analysis: the results of moisture, Aw, and brix degrees were: 4.29, 0.45 and 4.03, respectively. Thermogravimetric analysis showed that E. Camaldulensis is relatively stable at higher temperatures (up to 200 ° C ) and the active ingredients start to degrade. The hydrolysis of plant material was carried out by ultrasound at 37 ° C for 20 minutes. The fermentation process was performed at a temperature of 35 + / -2 ° C, 200 rpm for a 30 hour period, using the yeast Saccharomyces Cerevisiae and Candida Kefyr, and performing analysis of reducing sugars by the DNS. For both yeast analyses, the results showed that reducing sugars between lower longer fermentation xylose concentrations in the hydrolysate. This result indicates that the yeast was used xylose to produce xylitol. Saccharomyces Cerevisiae howed better efficiency consuming xylose 51.42 %. Incontrast, Candida Kefyr consumed 36.81 %, both over a period of 30 hours.